2002
DOI: 10.1097/00007890-200206270-00021
|View full text |Cite
|
Sign up to set email alerts
|

Intraportal infusion therapy as a novel approach to adult ABO-incompatible liver transplantation1

Abstract: Our experience has shown the feasibility of controlling rejection and other complications in adult ABO-incompatible liver transplantation under intraportal infusion therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
113
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(115 citation statements)
references
References 5 publications
1
113
0
1
Order By: Relevance
“…14,15 On account of these therapies, the outcomes of LDLT using an ABO-incompatible partial graft have become close to those obtained with an ABO-compatible graft. Naturally, the number of ABO-incompatible LDLTs performed will increase because of the shortage of deceased donor LTs, based on the feasibility of preparing recipients for elective LDLT, by administering Rituximab.…”
Section: Discussionmentioning
confidence: 98%
“…14,15 On account of these therapies, the outcomes of LDLT using an ABO-incompatible partial graft have become close to those obtained with an ABO-compatible graft. Naturally, the number of ABO-incompatible LDLTs performed will increase because of the shortage of deceased donor LTs, based on the feasibility of preparing recipients for elective LDLT, by administering Rituximab.…”
Section: Discussionmentioning
confidence: 98%
“…10 We used the hepatic arterial route for local infusion therapy because the arterial infusion has several merits over portal infusion. First, the lumen of the intrahepatic artery is much more narrow compared with that of the portal vein, making the graft arterial system more vulnerable to be thrombosed by AMR.…”
Section: Discussionmentioning
confidence: 99%
“…The turning point of ABO-I living donor liver transplantation (ABO-I LDLT) was in the 2000's when Tanabe et al reported the case of two adult patients who had undergone ABO-I LDLT [5]. The antirejection therapy included multiple perioperative plasmapheresis, splenectomy, systemic triple immunosuppressive regimen with tacrolimus, methylprednisolone, and cyclophophamide or azathioprine.…”
Section: Rituximabmentioning
confidence: 99%
“…In 1998, a Keio University group of researchers developed an anti-rejection regimen administered by portal vein infusion [5]. Their protocol included multiple perioperative plasma exchange, splenectomy, and a systemic triple immunosuppressive regimen consisting of tacrolimus, methylprednisolone, and cyclophosphamide or amathioprine.…”
Section: Local Infusion Therapymentioning
confidence: 99%